DISENTANGLING INDONESIAN BANKING COMPETITION BASED ON BUKU CLASSIFICATION: IMPLICATIONS ON BANK SOUNDNESS - Miryam B.L.S.K. Wijaya; Charvin Lim; Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2018)
ABSTRACTCompetition has long been debated as a vital factor determining banking performance and stability. The broad perspectives are divided into two streams, the ‘competition-fragility’ and ‘competition-stability’ view. Banking industry in Indonesia is experiencing consolidation waves as an effort to strengthen capital and enhance intermediation performance. The consolidation, however, inevitably alter the degree of competition. In this study, we propose a detailed assessment of competition effect through disentanglement amongst different bank clusters, particularly with respect to BUKU classification. The separation is done through Fixed Effect Vector Decomposition method, complemented by interaction variables. We found an indication that competition amongst Indonesian banks can be divided into two segments: the first containing BUKU1 and 2, while the latter BUKU3 and 4. Observing 57 banks using monthly data in 2006-2015, our study supports the competition-stability view, suggesting competition has positive influences on bank soundness. Adding more market power to the leader in each segment (BUKU2 and BUKU4, respectively) would have insignificant, if not malign, effect; the opposite for the challenger. Further, aside from competition, we found that interbank interaction promotes soundness.Keywords: competition; bank soundness; fixed effect vector decomposition